Effect of Green Manufacturing on Performance of Sugar Manufacturing in Western Kenya - Mercy Nafula Mwalati; Willis Otuya; Kelvin Machuki (Journal of Business and Social Review in Emerging Economies, 2025)
Purpose; The study focused on effects of green manufacturing on performance of sugar manufacturing firms in western Kenya.